Parametric Instability of Square Laminated Plates in Hygrothermal Environment. (1st August 2013) - Rath, Manoj Kumar; Sahu, Shishir Kumar
Abstract : The present paper investigates the parametric instability of square laminated plates subjected to periodic dynamic loadings in hygrothermal environment. The effects of various parameters like the increase in static load factor and the degree of orthotropy of simply supported composite plates at elevated temperatures and moisture concentrations on the principal instability regions are investigated using finite element method. The effects of transverse shear deformation and rotary inertia are used to study the antisymmetric angle-ply square plates. A simple laminated plate model is developed for the parametric instability of square laminated plates subjected to hygrothermal loading. A computer program based on FEM in MATLAB environment is developed to perform all necessary computations. The results show that instability of square laminated plates occurs for different parameters with an increase in temperature and moisture environment. The onset of instability occurs earlier, and the width of dynamic instability regions increases with a rise in temperature and moisture for different parameters. The effect of damping shows that there is a finite critical value of dynamic load factor for each instability region below which the square laminated plates cannot become unstable.